Different Responses in Root Water Uptake of Summer Maize to Planting Density and Nitrogen Fertilization - Gao, Yang; Chen, Jinsai; Wang, Guangshuai; Liu, Zhandong; Sun, Weihao; Zhang, Yingying; Zhang, Xiaoxian (Frontiers in Plant Science, 2022)
Modifying farming practices can be used with breeding to improve water and nutrient use efficiency by regulating root growth, but achieving this goal requires to phenotyping the root system including its architecture and ability to uptake water and nutrients from different positions in soil, which has been inhibited by the difficulty of in situ root measurement due to the opaque nature of the soil. Using stable isotopes and soil coring, this paper elucidates the responsive changes in root water uptake of a maize field to planting density and nitrogen fertilization in northern China. In the field experiment, we periodically measure root-length density, soil moisture and stable isotopes δ18O and δD in plant stem, soil water and precipitation concurrently, and the root water uptake is calculated based on mass balance of the isotopes and the Bayesian inference method coupled with the Markov chain Monte Carlo simulation. The results reveal that root water uptake is plastic and not proportional to root-length density, and that the change in water acquisition by roots along the soil profile is affected by nitrogen application more than by planting density. In particular, we find that low nitrogen application promotes roots to forage deep for nutrients thereby enhancing their water uptake from subsoil (below 60 cm), while increasing planting density benefits water acquisition from the topsoil. Data from all treatments show that root water uptake rate (y) increases with root-length density (x) but at a decreasing rate due to the increased root competition, and that their relationship fits to . These findings have imperative implications as they help our understanding of how plant density and fertilizer application can be manipulated to improve water and nutrient use efficiency in agricultural production.